Istiratijiyyat al-Dzaka’at al-Muta’addadah Ru’yah Jadidah li Tanmiyah al-Tadzawwuq al-Adaby fi al-Marhalah al-Tsanawiyah - Anaam, Abdulqawi; Abdul Ghani, Kamarulzaman bin; Abdul Rahman, Ahmad bin (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aimed to examine the effectiveness of multiple intelligence strategies in developing the literary appreciation of second-year secondary students in Yemen. The study adopted the quasi-experimental approach, deploying a two-group quasi-experimental design, an experimental and a control group. The sample of this study was represented by the second-year students of secondary school at Al-Farouq Primary Secondary School in Taiz governorate. There were 30 students in the experimental group and 29 students in the control group. The data for two correlated and two independent samples were analysed using a statistical program (SPSS, 28) with arithmetic means, standard deviations, and T tests. The results showed a statistically significant difference between the average scores of the experimental group students in the pre- and post-applications of the literary taste test, in favour of the post-application, with a very large effect size, in addition to the superiority of the experimental group over the control group in the post literary taste test. The results portrayed that teaching strategies based on the theory of multiple intelligence effectively developed the literary appreciation skills of second-year secondary students.